Investigating the Abnormal Presentation of Ureteropelvic Junction Obstruction in Adolescence: A Case Report: Ureteropelvic Junction Obstruction in Adolescence - Wexler, Ryan S.; Fuller, Leslie; Kelly, Kristen (Journal of Pediatric Nephrology, 2025)
Background and Aim: Ureteropelvic junction obstruction (UPJO) is a common cause of hydronephrosis and is typically diagnosed antenatally. About 70% of these cases will selfresolve; however, symptomatic children may present with abdominal pain (i.e. Dietl crisis), vomiting, rash, or fever. Case Presentation: A 14-year-old male patient presented with cyclical vomiting every two months for the past two years. The patient’s mother also described an eight-year history of headaches and intermittent abdominal pain. A renal magnetic resonance urography scan revealed decreased right kidney function and delayed cortex to ureter transit time. A pyeloplasty and stent placement were performed to correct the obstructing vessel. Conclusion: Clinical guidelines for abdominal pain and cyclical vomiting earlier in the patients’ healthcare may have led to an appropriate workup and treatment years before. We recommend physicians consider UPJO as a differential diagnosis in adolescent patients with cyclical vomiting and abdominal pain and consult the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition (NASPGHN) guidelines to better guide the diagnosis.